2011
DOI: 10.4269/ajtmh.2011.11-0013
|View full text |Cite
|
Sign up to set email alerts
|

Highly Virulent Leptospira borgpetersenii Strain Characterized in the Hamster Model

Abstract: A recent study by our group reported the isolation and partial serological and molecular characterization of four Leptospira borgpetersenii serogroup Ballum strains. Here, we reproduced experimental leptospirosis in golden Syrian hamsters (Mesocricetus auratus) and carried out standardization of lethal dose 50% (LD50) of one of these strains (4E). Clinical disease features and histopathologic analyses of tissue lesions were also observed. As results, strain 4E induced lethality in the hamster model with inocul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 25 publications
0
6
0
2
Order By: Relevance
“…[107][108][109] The hamster model has been thoroughly described, with diverse publications on the use of this species in leptospirosis vaccine studies. 3,106,110,111 Rats belonging to the Rattus genus were recognized as a reservoir host of the pathogenic Leptospira spp in the transmission cycle to humans. 112 Rats remain the most important source of transmission in urban settings.…”
Section: Discussionmentioning
confidence: 99%
“…[107][108][109] The hamster model has been thoroughly described, with diverse publications on the use of this species in leptospirosis vaccine studies. 3,106,110,111 Rats belonging to the Rattus genus were recognized as a reservoir host of the pathogenic Leptospira spp in the transmission cycle to humans. 112 Rats remain the most important source of transmission in urban settings.…”
Section: Discussionmentioning
confidence: 99%
“…Unexpectedly, no areas of intensive hemorrhage were observed in the lungs of challenged animals, which differs from previous studies reporting foci of intensive hemorrhage in L. interrogans -infected hamsters ( Nally et al., 2004 ; Villanueva et al., 2014 ). The absence of profuse pulmonary lesions could result from the high infectious dose used in our experiments: the hamsters could have died before the infection invaded the lungs ( Diniz et al., 2011 ). As for the single surviving hamster, a recent study has shown that females are more resistant than males to L. interrogans infection ( Gomes et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…(20,(39)(40)(41)(42)(43)(44)(45). Entre estos hallazgos resaltamos los estudios en hámster y tití común (Callithrix jacchus) con especies patógenas de diferente origen y bajo diferentes protocolos de infección.…”
Section: Discussionunclassified
“…Entre estos hallazgos resaltamos los estudios en hámster y tití común (Callithrix jacchus) con especies patógenas de diferente origen y bajo diferentes protocolos de infección. En estas infecciones se encontraron lesiones pulmonares y de riñón que variaban de leves a graves, semejantes a las encontradas en el presente estudio en el modelo de hámster infectado con L. santarosai (40)(41)(42)(43). Del mismo modo, Arean, et al, (39) en las necropsias de casos fatales en humanos, describieron diferentes grados de compromiso pulmonar, particularmente los caracterizados por áreas de hemorragia, edema y congestión alveolar, lo que se asemeja a lo encontrado en este estudio en el modelo de hámster-L. santarosai.…”
Section: Discussionunclassified